The effective evaluation of the guidance method which has the changed interception quantity that adaps to movement of target. - Định, Nguyễn Công; Hà, Trần Ngọc; Khoa, Nguyễn Ngọc (Journal of Computer Science and Cybernetics, 2012)
In this paper, the author assessed the effect of guidance law with minimum normal accelerator trajectory in the whole of guidance process and at the impact point by destructive range parameters. Base on real parameters of intermediate-range missile ammunition and typical properties of x93+x94 scan missile control system control observatory combining Matlab simulation of authors proved the effect of the new law.